PEMBINAAN PEMBINAAN BUDAYA RELIGIUS DAN SIKAP INTEGRITAS PADA PESERTA DIDIK ISLAMIC BOARING SCHOOL MAN TEMANGGUNG KABUPATEN TEMANGGUNG TAHUN AJARAN 2022/2023 - Arlindasari, Putri; Mufiq, Mufiq; Zaman, Badrus (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
This research aims to answer the questions that researchers found, namely 1). To find out about the development of religious culture. 2) To find out about fostering an attitude of integrity. 3). To analyze the supporting factors and inhibiting factors in fostering religious culture and an attitude of integrity in students at the Islamic Boarding School MAN Temanggung. Using descriptive qualitative research methods and used is field research. Research findings on the development of religious culture through the habit of creating a religious atmosphere. The form of achieving the development of an attitude of integrity is through coaching by the Islamic Boarding School management to student parents. Behind the success of fostering religious culture and an attitude of integrity, there are supporting factors.